2015
DOI: 10.1007/s00391-015-0949-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teriparatide on repair of femoral metaphyseal defect in ovariectomized rats

Abstract: Our findings suggest a positive effect of PTH on defect healing in ovariectomized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…A critical-sized bone defect is defined as an intraosseous wound that will not spontaneously heal completely without intervention, 28 the diameter of 3 mm considered as critical in animal model of OVX rat, 29 including already confirmed previous studies by our group. 19,30 The operative management of critical-size bone defects in humans is an outstanding problem in contemporary orthopedics and trauma surgery. To date, autologous bone graft is the gold standard to treat such injuries but this method is greatly restricted by important morbidities related to the bone graft collection procedure 31 and there is a crucial need for developing new bone substitutes.…”
Section: Discussionmentioning
confidence: 99%
“…A critical-sized bone defect is defined as an intraosseous wound that will not spontaneously heal completely without intervention, 28 the diameter of 3 mm considered as critical in animal model of OVX rat, 29 including already confirmed previous studies by our group. 19,30 The operative management of critical-size bone defects in humans is an outstanding problem in contemporary orthopedics and trauma surgery. To date, autologous bone graft is the gold standard to treat such injuries but this method is greatly restricted by important morbidities related to the bone graft collection procedure 31 and there is a crucial need for developing new bone substitutes.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Conversely, significant reduction of sliding of lag screw, femoral shortening, varus collapse, and incidence of cut-out of the lag screw was noted in patients who received teriparatide (Table 1 ). Tao et al 33 study 27 female Sprague–Dawley rats and concluded that 8 weeks of teriparatide use provides a positive effect on repair of femoral metaphyseal defect. This positive effect provides sufficient contact between fracture fragments to decreases excessive sliding of the lag screw and prevents subsequent complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown that PTPD by dual mechanism of action, influencing both bone formation activity and bone resorption. [8,9,44,45] PTPD up-regulate gene markers associated with osteoblast differentiation and an inhibitor of the Wnt pathway. [6,46] Successful attempt to use of TPTD even after revision surgery of nonunion has been published.…”
Section: Can Tptd Be An Alternative For Nonunion?mentioning
confidence: 99%
“…Its anabolic effect is given by the stimulation of the osteoblast, and fibroblast growth factor 2 is also up-reguhttps://doi.org/10.11005/jbm.2020.27.3.167 lated in TPTD treated individuals. [8][9][10] There has been previous reviews that suggest the role of TPTD as alternate to induce fracture healing. [11][12][13] However, to date, many clinical trials have been undertaken to elucidate the efficacy of TPTD for inducing fracture healing in several situations, such as atypical femoral fracture (AFF).…”
Section: Introductionmentioning
confidence: 99%